Modification of Polycaprolactone microspheres surface by ultra violet/ozone treatment to improve its hydrophilicity - Samsudin, Nurhusna; Hashim, Yumi Zuhanis Has-Yun; Jimat, Dzun Noraini; Sopyan, Iis; Arifin, Mohd Azmir; Mel, Maizirwan; Mohd. Salleh, Hamzah (2015)
Unloaded microspheres were prepared from Polycaprolactone (PCL) using an oil-in water emulsion solvent evaporation method. The microspheres with the size distribution in a range of 150-200 µm were then treated by exposed the microspheres under ultra violet irradiation and simultaneously aerated with ozone (UV/O3) to modify the surface of the beads. The experimental results on surface modification of PCL revealed that the UV/Ozone treatment introduced hydroxyl and carbonyl group on the beads surface and that was confirmed by FTIR analysis and water contact angle. The existence of carboxyl groups grafted on PCL surface was verified quantitatively by absorbance spectroscopy where Toluidine Blue O was employed to react with carboxyl groups to generate an absorbance at 625nm show that the surface of the microspheres had became more hydrophilic